Initiative for Environmentally Oriented Social Innovation Development in Wonogiri Through the Program Gajah Mungkur - Sugiyo; Rafif, Aji Sofyan; Mulyani, Sri (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
The Wonogiri Regency area, as the upstream and primary buffer zone of the Bengawan Solo watershed, is highly dependent on the sustainability of the Waduk Gajah Mungkur ecosystem. However, challenges in the form of sedimentation rates, waste generation, and the declining productivity of the agriculture, forestry, and fisheries sectors have triggered environmental degradation while simultaneously increasing the socio-economic vulnerability of surrounding communities. To address these issues, PT PLN Indonesia Power PLTA Wonogiri initiated the Program Gajah Mungkur (Gerakan Ajak Pilah Sampah untuk Menjaga Lingkungan Konservasi dan Pertanian Subur) as a form of social innovation that integrates reservoir conservation with the strengthening of the local economy. This study employs a qualitative approach using the framework of six stages of social innovation (prompts, proposals, prototypes, sustaining, scaling, and systemic change) to analyze the dynamics of the program. The findings demonstrate that this social innovation program, focused in Pokoh Kidul Village and Wuryorejo Sub-District, has successfully empowered vulnerable groups gradually and inclusively through the strengthening of bank sampah institutions, the development of fish-based MSMEs, and integrated farming designed within a circular economy scheme. Furthermore, this initiative also supports food security through the Makan Bergizi Gratis (MBG) program and the Taman Asuh Sayang Anak (TAMASYA) program, thereby reinforcing the integration of environmental, economic, and social aspects of communities around the reservoir. The program outcomes indicate multidimensional impacts, including controlling the sedimentation rate, enhancing business diversification, increasing household income, and fostering collective community awareness in maintaining the ecological functions of the reservoir. With these achievements, the Program Gajah Mungkur can be regarded as a social innovation practice that bridges ecological and economic aspects while simultaneously opening opportunities for adaptive replication in other reservoir areas in Indonesia.